2021
DOI: 10.3390/su13052487
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Confinement Due to COVID-19 in Spain on Anxiety, Sleep and Executive Functioning of Children and Adolescents with ADHD

Abstract: The outbreak and the quick expansion of SARS-CoV-2, from December 2019 to today, has forced countries around the world to resolve virus containment measures in order to slow down the contagion curve. Between these measures, the situation of lockdown, and the isolation or limitation of social contact between the citizens, there has been an unknown psychological impact. Certain groups (the elderly, children and teenagers, and the clinical population, for instance) arouse serious fears among professionals due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 67 publications
4
25
0
7
Order By: Relevance
“…ASD patients showed less changes in weekday-weekend risetime than both ADHD and controls, while children with ADHD reported higher delays in bedtime than the other groups. Our findings are supported by specific studies on these two clinical groups and controls [ 2 , 16 ], reporting delayed bedtime in children with ADHD [ 10 , 17 ] and a reduced sleep duration in both ADHD and ASD [ 9 , 10 , 13 , 15 , 22 ].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…ASD patients showed less changes in weekday-weekend risetime than both ADHD and controls, while children with ADHD reported higher delays in bedtime than the other groups. Our findings are supported by specific studies on these two clinical groups and controls [ 2 , 16 ], reporting delayed bedtime in children with ADHD [ 10 , 17 ] and a reduced sleep duration in both ADHD and ASD [ 9 , 10 , 13 , 15 , 22 ].…”
Section: Discussionsupporting
confidence: 86%
“…Since sleep patterns significantly changed during the lockdown in typically developing children and adolescents [ 2 , 5 , 6 , 12 ], similar or even worse changes in subjects with ADHD and ASD could be expected. Several studies [ 9 , 10 , 13 , 14 , 15 , 16 , 17 ] reported a high percentage of patients with ASD or ADHD that changed their sleep with a significant worsening of sleep quality and disturbances during the lockdown. Specifically, ASD children showed significant worsening of sleep disturbances, sleep duration, and sleep quality [ 14 , 15 ] and an increase in bedtime resistance, delay in falling asleep, and night awakenings [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-sectional COVID-19 studies have also demonstrated the relationship between the change of mental health and sleep due to the COVID-19 pandemic [ 21 , 26 , [33] , [34] , [35] , [36] ]. For instance, Hyun, Hahm [ 33 ] reported that the symptoms of depression and anxiety explained poor sleep quality in young adults during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Hyun, Hahm [ 33 ] reported that the symptoms of depression and anxiety explained poor sleep quality in young adults during the COVID-19 pandemic. Navarro-Soria and Real-Fernández [ 36 ] demonstrated that children and adolescents under home confinement had higher state anxiety than the non-confinement ones, and state anxiety could further impact sleep. Recently, a larger-scale study with 6882 participants (18–94 years) from 59 countries reported that poorer sleep health was highly associated with more severe depression and anxiety symptoms during the COVID-19 pandemic [ 35 ].…”
Section: Introductionmentioning
confidence: 99%